A CpG 1018 adjuvanted neuraminidase vaccine provides robust protection from influenza virus challenge in mice - Shirin Strohmeier; Fatima Amanat; John D. Campbell; Paula Traquina; Robert L. Coffman; Florian Krammer (npj Vaccines, 2022)
Abstract Influenza virus infections pose a significant threat to global health. Vaccination is the main countermeasure against influenza virus spread, however, the effectiveness of vaccines is variable. Current seasonal influenza virus vaccines mostly rely on the immunodominant hemagglutinin (HA) glycoprotein on the viral surface, which usually leads to a narrow and strain-specific immune response. The HA undergoes constant antigenic drift, which can lead to a dramatic loss in vaccine effectiveness, requiring the annual reformulation and readministration of influenza virus vaccines. Recently, it has been demonstrated that the subdominant glycoprotein, neuraminidase (NA), is an attractive target for vaccine development. Here, we tested a newly developed recombinant influenza virus N1 neuraminidase vaccine candidate, named N1-MPP, adjuvanted with CpG 1018, a TLR9 agonist. Additionally, N2-MPP and B-NA-MPP vaccine constructs have been generated to cover the range of influenza viruses that are seasonally circulating in humans. These constructs have been characterized in vitro and in vivo regarding their functionality and protective potential. Furthermore, a trivalent NA-MPP mix was tested. No antigenic competition between the individual NA constructs was detected. By adjuvating the recombinant protein constructs with CpG 1018 it was possible to induce a strong and robust immune response against the NA, which provided full protection against morbidity and mortality after high lethal challenges in vivo. This study provides important insights for the development of a broadly protective NA-based influenza virus vaccine candidate.